Criminology and the narrative turn. (August 2016) - Presser, Lois
This paper situates narrative criminology within criminology and the academy at large. Narrative criminologists ask how narratives, particularly narratives of the self, influence criminal and other harmful action. The idea that our stories shape our experiences is well developed in the humanities (literature, philosophy) and in the social sciences (anthropology, history, psychology, sociology). However, criminologists have caught on to that idea only recently, which is especially curious given abundant evidence of the impact of storied ideology on mass violence. This paper therefore addresses two critical questions: what is new and important about narrative criminology, and why has criminology only recently taken the narrative turn that other academic disciplines took decades ago?